On the question of the application of forensic methods in judicial activities - Борисенко, І. В. (Theory and practice of jurisprudence, 2016)
The article described the author’s vision of the individual issues of the forensic methods in judicial activities. Doctrinal approaches, that exist today, are analyzed and the author’s own position is expressed.